The Peculiarities of the Pedagogical Historiography in Austria till the Middle of the 19th Century - Halyna Oleksiv; Oksana Shyika (Pedagogical Discourse, 2013)
The article deals with the peculiarities of the pedagogical historiography in Austria till the middle of the 19th century. Characteristics of the main sources connected with the principles of the Austrian pedagogical historiography are given in the context of the historical development of the state. They are: narrative sources (journalistic, historical articles, folklore, literary works, chronicles etc.), deductive sources (works on teaching and education methods, textbooks, school regulations, courses of lectures etc.) and documentary sources (guidelines and instructions of government, statistics data etc.).